(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This qualitative research study was intended to find the thoughts, feelings and actions of school principals of secondary schools in the town of Selebi Phikwe about the leadership styles they use in their high-performing schools and how their educational leadership practices align to the 21 leadership responsibilities coined by Marzano et al. (2005). The study used a phenomenological research design. Semi-structured interviews were used for collecting data from six school principals purposefully selected, who maintained high student achievement in the high-performing secondary schools. The evidence presented in this study established that to be successful in high-performing schools, principals must develop a school culture of high expectations with a focus on student achievement. Principals must be good managers who are compassionate. Effective principals build the collective efficacy of their teams by building strong relationships through effective means of communication. The participants of the study highlighted building school culture and having a clear and concise vision as the most prevalent characteristics principals must possess. In high-performing schools, the development of a strong culture is intentional and aligned to strong student achievement. Effective principals develop teacher instructional capacity through mentorship and coaching programs to assuage the challenges of inexperienced teachers and also value relationships with students, parents and the community. Effective principals retain experienced teachers in their schools by building strong relationships. Focus and being data-driven were also identified as leadership responsibilities that an effective principal must practice in an environment of their high-performance. School principals must also master accountability systems.